Pengaruh Substitusi Tepung Cangkang Telur terhadap Daya Terima Oatmeal Cookies pada Remaja Usia 10–15 Tahun - Nabiilah Nuur’ainii; Annis Catur Adi (Lembaga Pengembangan Kinerja Dosen, 2026)
Calcium deficiency among Indonesian adolescents remains a nutritional concern that necessitates the development of food products utilizing alternative calcium sources. Eggshell powder has potential as a calcium fortification ingredient due to its high calcium content and abundance as food waste. This study aimed to analyze the effect of eggshell powder substitution on the organoleptic characteristics and acceptability of oatmeal cookies among adolescents aged 10–15 years. This experimental study used a Completely Randomized Design with four substitution levels: 0% (F0), 5% (F1), 6% (F2), and 7% (F3). Organoleptic quality testing was conducted by three trained panelists, while hedonic testing was performed by 30 adolescent panelists on selected formulas (F0, F2, F3), analyzed using the Friedman test (α = 0.05). Organoleptic quality results showed that F2 and F3 had characteristics closest to the control, while F1 showed higher negative attribute intensity in taste and texture parameters. Hedonic test results showed no significant differences between formulas across all parameters (p > 0.05), with mean scores ranging from 3.87 to 4.63 out of a scale of 5 (very much liked). Formula F3 is recommended as the best formula as it demonstrated acceptability comparable to the control while containing the highest calcium substitution level.